KONSEP JALAN KEHIDUPAN DAN JALAN KEMATIAN MENURUT MATIUS 7:13-14 - Gulo, Ribala Erni; Hendi, Hendi (GENEVA: JURNAL TEOLOGI DAN MISI, 2021)
Abstract:Choosing a way of life is the most important thing in the life of a believer. Why? For the only way of life is Christ, without Christ there is no life. Hendi stated that although believers practice all the Shari'a in Christianity, but without Christ it is useless and futile because it is not religion or Sharia that can save humans but Christ. However, in reality it is stated that some Christians or believers who have believed in Christ for years and even diligently worship prefer the way of death to the way of life. So it's not surprising, a student in the guise of a prospective servant of God hanged himself because he was tired of hearing a lot of people talking for the sake of his parents not being allowed to move churches and sell houses. In this case it is also stated that people who have known Christ for many years do not guarantee to choose the path of life. By looking at the problems above, what is the attitude of believers in responding to such cases? It seems that the lay church or believers can't answer this, because lay believers understand the way of life based on moral understanding and understanding that is too shallow not as taught by Christ. So one example in the text of Matthew 7:13-14 is the author's attention and analyzes the text so that it can produce 2 points. First: Enter through the door and the wide path to destruction. Second: The door and the narrow path leading to life. Third, the results of the text itself. And from these three points the author will explain how important the Concept of the Way of Life and the Way of Death according to the text of Matthew 7:13-14 and the implications for the lay congregation.Keywords: Way of life; Way of death, Christ.Abstrak:Memilih jalan hidup merupakan hal yang terpenting dalam kehidupan orang percaya. Mengapa? Karena jalan kehidupan satu-satu ialah Kristus, tanpa Kristus tidak ada kehidupan. Hendi menyatakan walaupun orang percaya menjalankan segala syariat dalam agama Kristen tapi tanpa Kristus maka percuma dan sia-sia sebab bukan agama atau syariat yang bisa menyelamatkan manusia melainkan Kristus.  Akan tetapi, secara realita dinyatakan bahwa sebagian orang Kristen atau orang percaya yang bertahun-tahun percaya Kristus dan bahkan rajin beribadah lebih memilih jalan kematian dibanding dengan jalan kehidupan. Maka tidak heran, seorang mahasiswa dalam status kedok calon hamba Tuhan gantung diri dikarenakan bosan mendengar banyak omongan orang demi kedua orang tua tidak memperbolehkan pindah gereja dan menjual rumah. Dalam hal ini pun dinyatakan bahwa orang yang telah mengenal Kristus bertahun-tahun tidak menjamin memilih jalan kehidupan. Dengan melihat adanya permasalahan diatas, lalu bagaimana sikap orang percaya dalam menanggapi kasus yang demikian? Sepertinya gereja atau orang percaya tidak bisa menjawab hal ini, dikarenakan orang percaya memahami jalan kehidupan berdasarkan pemahaman secara moral dan pemahaman yang terlalu dangkal tidak seperti yang diajarkan oleh Kristus. Maka salah satu contoh dalam teks (Matius 7:13-14) yang menjadi perhatian penulis dan menganalisis teks tersebut sehingga dapat menghasilkan 2 point. Pertama: Masuk melalui pintu dan jalan yang lebar menuju kehancuran. Kedua: Pintu dan jalan yang sempit menuju pada kehidupan. Ketiga, Hasil dari teks itu sendiri. Dan dari ketiga poin tersebut penulis menjelaskan seberapa penting Konsep Jalan Kehidupan Dan Jalan Kematian menurut teks (Matius 7:13-14) dan implikasi bagi jemaat kaum awam.Kata Kunci: Jalan kehidupan; Jalan kematian, Kristus.